The women who built Hollywood : 12 trailblazers in front of and behind the camera - Rubin, Susan Goldman (Calkins Creek, an imprint of Astra Books for Young Readers, 2023)
Twelve diverse actors, directors, writers, editors, designers, and producers fought against sexism, racism and prejudice to have their voices heard and changed the industry forever.